2010
DOI: 10.1111/j.1467-789x.2010.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

The levelling off of the obesity epidemic since the year 1999 – a review of evidence and perspectives

Abstract: The purpose was to investigate a possible levelling off in the obesity epidemic, by systematically reviewing literature and web-based sources. Eligible studies and data sources were required to have at least two measures of obesity prevalence since 1999. A literature and Internet search resulted in 52 studies from 25 different countries. The findings supported an overall levelling off of the epidemic in children and adolescents from Australia, Europe, Japan and the USA. In adults, stability was found in the US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
373
7
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(411 citation statements)
references
References 73 publications
(143 reference statements)
21
373
7
10
Order By: Relevance
“…Despite efforts applied to recognize this epidemic and to deal with, there is no decrease noted in its occurrence, but at least a leveling off in its prevalence [14]. Although, a stability of obesity in this young population from developed countries is supported by Rokholm et al [22], it must be kept in mind that the prevalence is higher than ever before.…”
Section: Obesity Prevalence and Risks In Children And Adolescentsmentioning
confidence: 93%
“…Despite efforts applied to recognize this epidemic and to deal with, there is no decrease noted in its occurrence, but at least a leveling off in its prevalence [14]. Although, a stability of obesity in this young population from developed countries is supported by Rokholm et al [22], it must be kept in mind that the prevalence is higher than ever before.…”
Section: Obesity Prevalence and Risks In Children And Adolescentsmentioning
confidence: 93%
“…Much has been published on the pattern by which increasing obesity prevalence spreads through populations; however, although there are signs that some sub-populations may be beginning to reverse the trend, [34][35][36] little is yet known about the sociodemographic pattern by which obesity may begin to decline. It is therefore plausible that young children may be among the first to emerge from the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…33 A recent review including studies from 25 countries found evidence that obesity prevalence may be 'levelling off' in some groups, although there was substantial heterogeneity in trends, very few apparent decreases, and in contrast to this study, concluded that this trend was less evident in low SES populations. 34 Tracking of overweight and obesity from early childhood through later childhood years and into adulthood has been established in previous studies. 6 Overweight and obesity in young children therefore have the potential to significantly impact on health status throughout the lifespan, despite the lack of obvious immediate health consequences of excess weight during early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the association between SEP and body weight in high-income countries (18,19) show that adults from disadvantaged backgrounds are more likely to be overweight or obese, with the relationship being consistently strong and graded for women and somewhat weaker and less consistent for men. Negative associations between SEP and body weight in high-income countries have also been observed in childhood (20,21) .…”
Section: Current Evidence On Socio-economic Inequalities In Diet and mentioning
confidence: 99%